(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
In many countries, goat (Aja) rearing is well organized and is an essential part of living in terms of contributing to the economic structure as well as nutrition. Goat milk (Aja Dugdha) is rich source of protein, vitamins, enzymes and mineral content and most of them are present in higher percentage than that of other commonly consumed milk. For instance, it contains 13% more calcium, 47% more vitamin A and 25% more vitamin B6 than cow’s milk. It has better digestibility, alkalinity and buffer capacity than milk of other animals and also possesses numerous therapeutic properties viz. Anticancer, hepato-protective, cardio-protective and antihypertensive etc. Classical texts of Ayurveda also embrace its nutritive and therapeutic potential and indicated it in management of different diseases like Atisara (diarrhoea), Jwara (fever), Rajyakshma (tuberculosis), Kshaya, Shosha (atrophy/emaciation) etc. Methodology: Different scientific databases like Web of Science, Scopus etc. along with Ayurveda texts viz., Charak Samhita, Kashyap Samhita etc were searched in order to extract data pertaining to goat milk. Results: The present study revealed that in Ayurveda, goat milk has been indicated in the management of more than 20 disease conditions and conventional studies also reported more than 15 pharmacological properties of goat milk. Discussion & Conclusion: It has been found that the therapeutic and nutritive value of goat milk has been extensively studied in Ayurveda and conventional science as well. It’s easy to digest and have a better composition of vitamins, fatty acids, protein and minerals than other available milks. Therefore, it can be a used a most appropriate alternative to human and cow milk but should with caution as it lacks sufficient quantity of iron, folate and vitamins C etc.